New tricks for metastasis-associated macrophages - Qian, Bin-Zhi (BioMed Central, 2012)
Recent studies on breast cancer lung metastasis have identified a new mechanism of tumor cell survival via signaling provided by metastasis-associated macrophages. Targeting these specialized host immune cells and their specific signals provides an attractive and potential therapeutic approach for treating the disease.